2020
DOI: 10.1089/sur.2020.097
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Anesthesiology Specialists and Residents toward Patients Infected with the Novel Coronavirus (COVID-19): A National Survey Study

Abstract: A total of 346 anesthesiology specialists and residents participated in the study. Although the majority of the participants exhibited the correct attitudes toward airway management, research assistants with little professional experience were observed to be undecided or had the tendency to make incorrect decisions. Conclusions: The COVID-19 pandemic is spreading rapidly worldwide. The incidence of COVID-19 cases is increasing daily, and this disease can cause patient death. Anesthesiology specialists and resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 11 publications
0
66
0
14
Order By: Relevance
“…The SARS pandemic in 2002 had a mortality rate of 11%, whereas the Middle Eastern respiratory syndrome in 2012 had a mortality rate of 35%-50%. 3 In contrast, the mortality rate for COVID -19 worldwide is estimated at around 4%, being slightly lower in the US at 2.3%. 1,3 Never has the role of public health officials been more appreciated than what has been demonstrated in this pandemic, as these experts in communicable disease strive to protect the populace.…”
Section: Scope Of Diseasementioning
confidence: 96%
See 3 more Smart Citations
“…The SARS pandemic in 2002 had a mortality rate of 11%, whereas the Middle Eastern respiratory syndrome in 2012 had a mortality rate of 35%-50%. 3 In contrast, the mortality rate for COVID -19 worldwide is estimated at around 4%, being slightly lower in the US at 2.3%. 1,3 Never has the role of public health officials been more appreciated than what has been demonstrated in this pandemic, as these experts in communicable disease strive to protect the populace.…”
Section: Scope Of Diseasementioning
confidence: 96%
“…3 In contrast, the mortality rate for COVID -19 worldwide is estimated at around 4%, being slightly lower in the US at 2.3%. 1,3 Never has the role of public health officials been more appreciated than what has been demonstrated in this pandemic, as these experts in communicable disease strive to protect the populace. Most impressive has been their directives on social distancing, which has been clearly shown to reduce exposure, slow the onslaught of new cases, and control the demands on our healthcare system.…”
Section: Scope Of Diseasementioning
confidence: 96%
See 2 more Smart Citations
“…As of April 20, 2020, already seven (7) papers on the topic of tracking and forecasting COVID-19 using Google Trends data have been published, according to PubMed (advanced search: covid AND google trends) [22], monitoring, analyzing, or forecasting COVID-19 in several regions like Taiwan [23], China [24][25], Europe [26][27], USA [27][28], Iran [27,29]. Note that for Twitter publications related to the COVID-19 pandemic, eight papers (8) are online up to this point (PubMed advanced search: covid AND twitter [22]), published from March 13 to April 20, 2020 [30][31][32][33][34][35][36][37]. Table 1 consists of the systematic reporting of COVID-19 Google Trends studies, in the order of the reported publication date.…”
Section: Cases Deathsmentioning
confidence: 99%